2017
DOI: 10.1530/rep-17-0322
|View full text |Cite
|
Sign up to set email alerts
|

Implications of microRNA dysregulation in the development of prostate cancer

Abstract: MicroRNAs (miRNAs) are non-coding small RNAs that target mRNA to reduce protein expression. They play fundamental roles in several diseases, including prostate cancer (PCa). A single miRNA can target hundreds of mRNAs and coordinately regulate them, which implicates them in nearly every biological pathway. Hence, miRNAs modulate proliferation, cell cycle, apoptosis, adhesion, migration, invasion and metastasis, most of them constituting crucial hallmarks of cancer. Due to these properties, miRNAs emerged as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 122 publications
0
42
0
Order By: Relevance
“…Multiple miRNAs have been observed to be involved in several crucial processes in PCa, such as cell proliferation, apoptosis, invasion and metastasis [9, 12, 14, 15, 17]. The tumor suppression activity of miR-1-3p during tumorigenesis has been well-characterized in several cancers, including colorectal cancer [20], bladder cancer [22] and prostate cancer [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNAs have been observed to be involved in several crucial processes in PCa, such as cell proliferation, apoptosis, invasion and metastasis [9, 12, 14, 15, 17]. The tumor suppression activity of miR-1-3p during tumorigenesis has been well-characterized in several cancers, including colorectal cancer [20], bladder cancer [22] and prostate cancer [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…We also described for the first time that CTBP1 modulates multiple miRNAs in PCa from MeS mice that are involved in several pathways related to cancer development and progression. The importance of miRNAs in PCa has already been widely reported; however, there are few reports showing miRNA modulation by CTBP1. Indeed, our group demonstrated that CTBP1 modulates several miRNAs in BrCa, and Chakravarthi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in miRNA expression in PCa have been reviewed and described below. miRNAs upregulated by AR in PCa include miR-21, miR-27a, miR-32, miR-125b, miR135a, miR-141 and AR overexpression in PCa downregulates miR-99a (Massillo, et al 2017). miR-125b is the most overexpressed miRNA in PCa and downregulates apoptotic genes including BAK1.…”
Section: Dysregulation Of Mirnas In Pcamentioning
confidence: 99%
“…Other oncomiRs overexpressed in PCa are miR-21, miR-32, miR-221, miR-222, miR-181, miR-18a, and miR-429 (reviewed in (Kanwal, et al 2017)). "Andro-miRs": let-7c, miR-31, miR-124, miR-185, miR-205, and miR-488 downregulate AR expression (Massillo et al 2017). Notably, the top four downregulated miRNAs in PCa tissues are miR-187, miR-205, miR-222, and miR-31 (Fuse, et al 2012).…”
Section: Dysregulation Of Mirnas In Pcamentioning
confidence: 99%
See 1 more Smart Citation